Loneliness In Elderly Inmates At Class Iia Correctional Institution Banjarmasin - Imaduddin, Ikhlasul Amal; Aulia, Qisthina (UNIVERSITAS PAKUAN, 2024)
Abstract This study explores the condition of loneliness among elderly prisoners at Class IIA Banjarmasin Correctional Facility. A qualitative approach with a descriptive narrative design was used to understand the subjective experiences of elderly prisoners. Data were collected through in-depth interviews and observations of elderly prisoners, assisting inmates and Kasubsi Bimkemaswat of Class IIA Banjarmasin Correctional Facility , using purposive sampling. Data analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing, with validity tested using data source triangulation. The results show that emotional loneliness among elderly prisoners is caused and can be analyzed by aspects such the loss of intimate relationships, lack of attachment figures, feelings of emptiness, and abandonment. Social loneliness arises from superficial friendships, boredom, environmental changes, and rejection. Proposed intervention programs include religious approaches and group discussions between elderly prisoners, psychologists, and religious figures, aimed at reducing feelings of loneliness by enhancing emotional and social support. Keywords: emotional loneliness, social loneliness, elderly prisoners.